2020
DOI: 10.26603/ijspt20200034
|View full text |Cite
|
Sign up to set email alerts
|

Scoring Performance Variations Between the Y-Balance Test, a Modified Y-Balance Test, and the Modified Star Excursion Balance Test

Abstract: Background:The Modified Star Excursion Balance Test (MSEBT) and the Y-Balance Test-Lower Quarter (YBT-LQ) are utilized to assess dynamic postural stability. These assessments cannot be used interchangeably secondary to kinematic variations and performance differences. A Modified Y-Balance Test-Lower Quarter (MYBT-LQ) was developed to determine if a modification allows performance scores to be directly compared to the MSEBT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…Most clinicians and researchers regularly refer to YBT when describing the test despite there being a trademarked name of a device developed by Plisky et al 18 (see the specific section below). When carefully analyzing the literature, studies could either refer to SEBT, 10 mSEBT, 5 YBT, 27 or even the Y-Balance Test-Lower Quarter (YBT-LQ) 28 in the title or abstract although the testing procedure was similar.…”
Section: An Overview Of Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Most clinicians and researchers regularly refer to YBT when describing the test despite there being a trademarked name of a device developed by Plisky et al 18 (see the specific section below). When carefully analyzing the literature, studies could either refer to SEBT, 10 mSEBT, 5 YBT, 27 or even the Y-Balance Test-Lower Quarter (YBT-LQ) 28 in the title or abstract although the testing procedure was similar.…”
Section: An Overview Of Proceduresmentioning
confidence: 99%
“…40 However, it seems that results obtained with the YBT ™ are not systematically comparable with those obtained with the standard SEBT. 25,28,32 Fullam et al 31 recently detailed that main differences related to ANT direction with the YBT ™ leading to significant lower values compared with ANT direction of the SEBT. Similarly, Ko et al 41 reported significant differences between mSEBT and YBT in individuals with chronic ankle instability in ANT and PM directions.…”
Section: The Ybt™ Devicementioning
confidence: 99%
“…The YBT-LQ evaluates the dynamic stability, strength, and balance in various directions during a single-limb stance as the opposite leg extends in the anterior, posteromedial, and posterolateral planes. Participants were allowed to have two practice trials per lower extremity without shoes and socks to decrease the external stability of the ankle provided by their shoes [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Data from this study were collected at multiple locations using a standardised protocol as part of a preseason assessment of musculoskeletal function in male soccer players [14]. The measurement of the length of both lower limbs was performed following the test normalization and previous studies [24,25], that is, from the anterosuperior iliac spine to the most distal point of the tibial malleolus. A tape measure with one side graduated in centimetres (cm), a length of 2 m and a width of 2 cm (Lufkin W606PM) was used in this protocol.…”
Section: Instruments and Proceduresmentioning
confidence: 99%